Perceived organizational support (POS) and the career success among academician in Malaysian Universities / Siti Meriam Ali and Mohd Rizaimy Shaharudin - Ali, Siti Meriam; Shaharudin, Mohd Rizaimy (Universiti Teknologi MARA, Kedah, 2016)
The purpose of this study is to investigate the influence of percieved organizational support (POS) on subjective and objective career success, aiming at career success among Malaysia academician. The sample of this study consisted of 100 lecturers from one of the higher learning institution in Malaysia. The findings indicated that partial relationships exists between perceived organizational support with the career success. Perceived organizational support was significantly and positively related to the subjective career success (career satisfaction) but not the objective career success (number of promotion).